Risk factors for stroke on left ventricular assist devices. Issue 6 (17th May 2018) - Bishawi, Muath; Joseph, Jeremy; Patel, Chetan; Schroder, Jacob; Daneshmand, Mani; Bowles, Dawn; Rogers, Joseph; Milano, Carmelo
Abstract: Background: Patients with end‐stage heart failure on left ventricular assist devices (LVADs) are predisposed to a high incidence of stroke. Preoperative factors associated with increased stroke risk are poorly understood. Methods: We performed a single‐center retrospective review of all patients from 2009 to 2014 in whom a rotary flow LVAD was implanted. All patients with symptoms of a cerebrovascular event underwent a non‐contrast head computed tomography scan. Logistic regression was used to determine factors associated with stroke both on univariate and multivariable analysis. Results: A total of 390 patients were retrospectively analyzed and of those 61 (15.6%) had a stroke at an average follow‐up of 3.5 ± 1.6 years. The majority were male (72%) and were treated a priori as destination therapy (73%). The proportion of patient receiving a centrifugal flow pump was 23% compared to 77% receiving an axial flow pump. For those patients who experienced a stroke and then died, the average time from stroke to death was 158 ± 296 days. Of the 61 patients who had a stroke, 38 (62%) died ( P  < 0.001 compared to death rate without a stroke). On Cox regression analysis, a history of cerebrovascular accident (CVA), hyperlipidemia, and history of venous thromboembolism (VTE) were independently associated with stroke while on LVAD support. Conclusion: Postoperative stroke after LVAD implantation was associated with higher mortality. A history of previous CVA, VTE, and hyperlipidemia were independently associated with stroke while on LVAD support.